Penerapan Pendekatan Saintifik Berbasis 4C Untuk Meningkatkan Hasil Belajar Siswa Materi Aktivitas Manusia - Widayati, Sri (Inovasi: Jurnal Diklat Keagamaan, 2020)
This study aims to determine the increase in student learning outcomes in human activity materialthrough the application of 4C-based scientific approaches (communication, collaborative, critical thinking,and creativity) in class VII B of SMP Negeri 1 Mojoanyar Semester 2 in the 2019/2020 academic year. Thisresearch is a classroom action research (CAR) conducted in January - February 2020 through two cycles witheach cycle consisting of 4 stages of research, namely planning, implementation, observation andreflection. The subjects of this study were 32 students of class VII B of SMP Negeri 1 Mojoanyar. The resultsshowed that learning by applying a 4C-based scientific approach could improve the learning outcomes ofGrade VII B students of SMP Negeri 1 Mojoanyar on Social Sciences (IPS) lessons with human activitymaterial. These results can be seen from several indicators, including: [1] increasing the implementationof lesson plans from 3.08 in the first cycle to 3.50 in the second cycle, [2] student learning test resultsshow an increase in completeness classically 78.13 % in the first cycle to 87.50% in the second cycle , [3]student activity shows student-centered learning activities in both cycles with a percentage of the activityof 91.89% in the first cycle increased to 94.44 % in the second cycle.